A Process of Developing an HRM Framework Based on Qualitative Study in Technology Companies in Bangladesh and Malaysia - Andalib, Tarnima Warda (Beykent University, 2014)
In the corporate world, humans are treated as ‘manpower’ or ‘resources that utilize other resources, however, this cannot be the only identity of humans or employees of the company. Rather, it must be considered that these employees are humans and humans have got certain rights those are to be fulfilled irrespective of every situation. Humans are beings not just mere resources. This is the time to understand this truth. Technological change has triggered and increased the standard of living but at the same time has deteriorated the humane values and inspired a profligate life style; therefore, the Standardized Human Rights policies like Universal Declaration of Human rights (UDHR) & International Labour Organization (ILO) need to be implemented in the organization culture by understanding the attitudes, attributes of human resources. The purpose of this Study is to investigate the HRM policies of the Technology Companies of Malaysia & of Bangladesh and to identify all the components and integrate all those components with the standardized Human Rights platforms, which are UDHR, ILO etc. To look for the behavior, attitude and analytical option of humans working inside the company due to technological advancements, changes and implemented HRM policies in the organization.